Bridging the Gap? Scale and Development-led Archaeology in England Today. (1st June 2013) - Thomas, Roger M
<x xml:space="preserve">Abstract</x> Abstract Large development-led archaeological investigations can help to 'bridge the gap' in scales between 'point-data' and 'landscape-scale' surveys, placing the former in a wider context and aiding interpretation of the latter. Examples from southern England show how large-area excavations, geophysical surveys and field evaluations all provide highly detailed information over extensive areas. Among other things, work on this scale can confirm the existence of 'blank' areas, which contain few archaeological remains but which would have been important parts of the overall landscape in the past. Large-scale development-led work can contribute to archaeological interpretation of the landscape across a broad range of scales.